A morphological and molecular study of proposed early forms of traditional serrated adenoma. Issue 6 (9th October 2018) - Bettington, Mark; Rosty, Christophe; Whitehall, Vicki; Leggett, Barbara; McKeone, Diane; Pearson, Sally‐Ann; Walker, Neal
Abstract : Aims: Traditional serrated adenoma (TSA) is the least common subtype of serrated colorectal polyp. Large protuberant lesions are easily recognised; however, the origins of TSAs are not known, and early forms have not been described. Some large TSAs present with a flat 'shoulder' component surrounding the central protuberant component. We hypothesised that small polyps with the same histology as these shoulder regions may represent early TSAs. Thus the primary aim of the study is to describe the histology of these presumptive early TSAs. Methods and results: We collected 70 small (<10 mm) polyps that may represent early TSAs on the basis of typical TSA cytology covering the luminal surface. We also identified 12 large TSAs with a shoulder component resembling these small polyps. The study polyp patients had a mean age of 58 years, and 54% were female; the polyps had a mean diameter of 4.1 mm and were predominantly distal (71%). Morphologically, slit‐like serrations were present in 81%, ectopic crypt formations were present in 67%, and a villous component was present in 47%. These histological features were similar to those of the 12 shoulder lesions. Immunohistochemical stains showed an absence of β‐catenin nuclear expression in 96% of the small polyps, retained expression of MLH1 in 100%, and Ki67 positivity restricted to the crypt bases and ectopic crypt formations. BRAF and KRAS mutations were identified in 47% and 31% of the polyps, respectively. BRAF ‐mutated polyps were more likely than KRAS ‐mutated polyps to arise in a precursor polyp (82% versus 18%, P < 0.001), and were more likely to have slit‐like serrations (100% versus 73%, P = 0.003). Conclusions: These morphological, immunohistochemical and molecular findings are similar to what has been reported in large TSAs, and support the hypothesis that these polyps represent early forms of TSA.